Gas diffusion through variably-water-saturated zeolitic tuff: Implications for transport following a subsurface nuclear event. (September 2022) - Neil, Chelsea W.; Boukhalfa, Hakim; Xu, Hongwu; Ware, S. Douglas; Ortiz, John; Avendaño, Sofia; Harp, Dylan; Broome, Scott; Hjelm, Rex P.; Mao, Yimin; Roback, Robert; Brug, William P.; et al.
Abstract: Noble gas transport through geologic media has important applications in the characterization of underground nuclear explosions (UNEs). Without accurate transport models, it is nearly impossible to distinguish between xenon signatures originating from civilian nuclear facilities and UNEs. Understanding xenon transport time through the earth is a key parameter for interpreting measured xenon isotopic ratios. One of the most challenging aspects of modeling gas transport time is accounting for the effect of variable water saturation of geological media. In this study, we utilize bench-scale laboratory experiments to characterize the diffusion of krypton, xenon, and sulfur hexafluoride (SF6 ) through intact zeolitic tuff under different saturations. We demonstrate that the water in rock cores with low partial saturation dramatically affects xenon transport time compared to that of krypton and SF6 by blocking sites in zeolitic tuff that preferentially adsorb xenon. This leads to breakthrough trends that are strongly influenced by the degree of the rock saturation. Xenon is especially susceptible to this phenomenon, a finding that is crucial to incorporate in subsurface gas transport models used for nuclear event identification. We also find that the breakthrough of SF6 diverges significantly from that of noble gases within our system. When developing field scale models, it is important to understand how the behavior of xenon deviates from chemical tracers used in the field, such as SF6 (Carrigan et al., 1996). These new insights demonstrate the critical need to consider the interplay between rock saturation and fission product sorption during transport modeling, and the importance of evaluating specific interactions between geomedia and gases of interest, which may differ from geomedia interactions with chemical tracers. Highlights: Xe, Kr, and SF6 diffusion through zeolitic tuff are measured. Preferential sorption interactions between Xe and zeolites slows Xe breakthrough. Low partial water saturation greatly reduces Xe sorption by zeolites. Caution is advised for using SF6 as a tracer to predict Xe transport in zeolite-containing lithologies.